2022
DOI: 10.1371/journal.pbio.3001532
|View full text |Cite
|
Sign up to set email alerts
|

Colon stroma mediates an inflammation-driven fibroblastic response controlling matrix remodeling and healing

Abstract: Chronic inflammation is often associated with the development of tissue fibrosis, but how mesenchymal cell responses dictate pathological fibrosis versus resolution and healing remains unclear. Defining stromal heterogeneity and identifying molecular circuits driving extracellular matrix deposition and remodeling stands to illuminate the relationship between inflammation, fibrosis, and healing. We performed single-cell RNA-sequencing of colon-derived stromal cells and identified distinct classes of fibroblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 131 publications
1
51
0
1
Order By: Relevance
“…However, many of the original insights into IL11 biology were based on the use of rhIL11 in the mouse, which has unexpected effects [7,8]. This discovery underpins the realization that IL11 is profibrotic [46,9,11] whereas the earlier literature had reported it as anti-fibrotic [3,3941]. We suggest that, as it was for fibrosis, the role for IL11 in inflammation is misinterpreted.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, many of the original insights into IL11 biology were based on the use of rhIL11 in the mouse, which has unexpected effects [7,8]. This discovery underpins the realization that IL11 is profibrotic [46,9,11] whereas the earlier literature had reported it as anti-fibrotic [3,3941]. We suggest that, as it was for fibrosis, the role for IL11 in inflammation is misinterpreted.…”
Section: Discussionmentioning
confidence: 96%
“…Newer data challenge the earlier literature on the role of IL11 in inflammation as its activity in fibroblasts is now thought to promote stromal-driven inflammation in colitis, synovitis and cancers [11,1719]. Furthermore, expression of IL11 in vascular smooth muscle cells is linked with inflammation [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the profibrotic effects of IL11, recent data have shown that IL11 signalling plays an important role in stromal-driven inflammation in the lung, colon and liver [ 19 , 25 , 32 , 33 ]. Although we did not investigate the specific role of IL11 in the immune response in pancreatitis, we found that blocking IL11 signalling had anti-inflammatory effects and reduced IL6, IL1β and TNFα protein levels as well as diminishing NF-κB and STAT3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the emerging studies using scRNA-seq have significantly improved our understanding of the heterogeneity and the distinct role of diverse subsets of intestinal MSCs in regulating mucosal homeostasis and immunity by providing different niche signals under both physiological and inflammatory conditions ( 37 , 38 ). For instance, Jasso et al recently identified distinct subpopulations of stromal fibroblasts with gene signatures that are differentially regulated by chronic inflammation through scRNA-seq analysis of colon-derived mesenchymal stromal cells, thus providing mechanistic insight into how inflammation affects the function and behavior of intestinal MSCs and their crucial role in orchestrating mucosal tissue remodeling and healing ( 41 ).…”
Section: Pathogenic Mechanism Of Ibdsmentioning
confidence: 99%